Marked - Tingey, Sue (Jo Fletcher Books, 2015)
Lucky deSalle can see ghosts, but it's daemons she should be worried about. With no family and very few friends, Lucky's psychic ability has always made her an outcast. The only person she can rely on is Kayla, the ghost girl who has been with her since she was born. But Kayla is not all that she appears. Then again, neither is Lucky...